An Unusual Case of Campylobacter jejuni Gastroenteritis Presenting with Acute Reversible Encephalopathy in an Immunocompetent Host - Irma Huayanay; Leonardo Pozo; Salman Bangash; Denisse Ramirez; Luis Rosas; Renzo Arauco Brown (Case Reports in Infectious Diseases)
Campylobacter jejuni gastroenteritis is the most frequent organism associated with acute infectious diarrhea worldwide. The clinical presentation involves fever, diarrhea, rigors, and myalgias. Other extraintestinal symptoms that have been described involve delirium and other neurological complications, and the most well-known is Guillain-Barré, where there is cross-reactivity between the gastrointestinal tract and the brain. Despite previously described multiple neurological complications, there is a lack of clinical data on the association of Campylobacter-related gastroenteritis with acute encephalopathy in immunocompetent patients. The type of population, immunocompetent stage, and unfamiliarity with the clinical presentation makes this a challenging diagnosis for clinicians. We report a case of Campylobacter gastroenteritis associated with acute encephalopathy in an immunocompetent patient.